KONSEP TARBIYAH, TA’LIM DAN TA’DIB DALAM DUNIA PENDIDIKAN ISLAM - Frarera, Andre Nova (STIT Al-Ittihadiyah Labuhanbatu Utara, 2023)
In the Islamic world, education has various terms with different meanings, including tarbiyah, ta'lim, and ta'dib. This paper aims to analyze the differences between the three terms in the world of Islamic education, namely, tarbiyah, ta'lim, and ta'dib and how these three terms are implemented in the world of education. This paper is qualitative in nature with the use of the literature study method in writing its contents, in order to open data with data collection techniques through books and articles that have linear discussions on the main topic. Based on the data collection in this study, it was found that (1) tarbiyah, ta'lim, and ta'dib have the same meaning, namely education. (2) The application in education of the terms tarbiyah, ta'lim, and ta'dib has a difference in the emphasis on understanding. (3) In the current world of education, tarbiyah, ta'lim, and ta'dib can be implemented.